2020
DOI: 10.3390/nu12010150
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cellular Uptake of Polyunsaturated Fatty Acids and Phytosterols from Natural Micellar Oil

Abstract: The transport of hydrophobic compounds to recipient cells is a critical step in nutrient supplementation. Here, we tested the effect of phospholipid-based emulsification on the uptake of hydrophobic compounds into various tissue culture cell lines. In particular, the uptake of ω-3 fatty acids from micellar or nonmicellar algae oil into cell models for enterocytes, epithelial cells, and adipocytes was tested. Micellization of algae oil did not result in adverse effects on cell viability in the target cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Bile acids could influence PUFA digestion and absorption as Rohrl et al 63 showed that cellular uptake of PUFA was selectively improved by micellization of an oil. Changes in BA metabolism were, indeed observed after applying the three dietary treatments in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids could influence PUFA digestion and absorption as Rohrl et al 63 showed that cellular uptake of PUFA was selectively improved by micellization of an oil. Changes in BA metabolism were, indeed observed after applying the three dietary treatments in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…GC‐MS analysis was performed as described previously. [ 34 ] Full scans from m / z 40 to 400 were recorded and SIM scans at m / z 55, 67, 74, and 79 were used for quantification with the Supelco 37 Component FAME Mix (Sigma–Aldrich, St. Louis, MO, USA) as an external standard.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, immortalized human intestinal cell lines such as CaCo-2 and LS-180 have been established as convenient tools to study drug absorption and their interplay with transporting and metabolizing enzymes [ 15 ]. They have been successfully utilized by our group, for instance, to investigate the uptake of micellated algae oil [ 16 ].…”
Section: Introductionmentioning
confidence: 99%